Environmental Practices and Competitiveness - Salem, Milad Abdelnabi; Hasnan, Norlena; Osman, Nor Hasni; Shamsudin, Mohd Farid; Iqbal Hussain, Hafezali; Salem, Lokman; Sheikh Khairuddin, Sheikh Muhamad Hizam (International Journal of Current Research, 2014)
Although considerable amount of the literature related to examination the link between environmental protection issues and the performance, different results and mixed outputs have been articulated by these studies, and previous research yet to investigate approach of corporate environmental practices and competitiveness. The purpose of this paper was to disaggregate corporate environmental activities into six dimensions (green practices, employees' involvements, en process and examine how each dimension would affect competitiveness among manufacturin While all corporate environmental activities were proposed to have positive effects, the results revealed that each dimension has a different effect on competitiveness. Such results may assess the industrial corporation by directing their eff competitiveness